Perancangan dan pengembangan connector wheelchair sebagai alat bantu tuna daksa - Happy Ernesto Putra; Sunday Noya (Institut Seni Indonesia Yogyakarta, 2018)
In recent years the world community has begun to pay attention to the rights of disabled people not least the Government and the people of Indonesia. Much effort has been made from law enforcement to the provision of assistance to disabled people. The object of this research is disabled people in Malang. There is still a lack of facilities for disabled in terms of accessibility and uniqueness in Indonesia that are able to sell motorcycles with a large number, as well as with the development of smartphone technology that gave rise to the phenomenon of GoJek provides the idea to make transportation equipment safe, comfortable and cheap for disabled people tuna daksa. The tool is a wheelchair that can be attached to a motorcycle (connector wheelchair). The design and development of wheelchair connector is done using QFD phase 1 and Ergonomic method. The benefit of QFD 1 is to get wheelchair connector specifications. The output of this research is 3D design. Key words: disabled people, QFD, ergonomic, product design